The Effect of Peppermint Aromatherapy on the Degree of Nausea and Vomiting in Pregnant Women in the First Trimester at the Independent Practice of Midwife (TPMB) Yusnita Purwasari, Karawang Regency, Indonesia - Yusnita Purwasari; Qurotul ‘Aini (HM Publisher, 2023)
Pregnancy is a physiological condition that can be followed by pathological processes that will threaten the condition of the mother and fetus. During pregnancy, problems can occur that a mother does not want. Nausea and vomiting are complaints that are often experienced by pregnant women in the first trimester due to an increase in HCG in the pregnant woman's body. If this situation continues, it will have an impact on the pregnancy and fetal growth process. This study aimed to identify the effect of peppermint aromatherapy on reducing nausea and vomiting in pregnant women. The design of this research is experimental research pre-test and post-test one group. Sampling technique with purposive sampling where every first trimester pregnant woman who underwent a pregnancy check-up who met the inclusion criteria was included in this study. The results showed that there was a decrease in the degree of nausea and vomiting in research subjects before and after being given the intervention (2.12 ± 0.11 Vs 1.11 ± 0.13), p < 0.05. In conclusion, there is influence giving aromatherapy peppermint in reducing the degree of nausea and vomiting in first trimester pregnant patients at TPMB Yusnita Purwasari, Karawang Regency, Indonesia.